Menstrual hygiene management practice among adolescent girls: an urban-rural comparative study in Rajshahi division, Bangladesh - Md. Abu Tal Ha; Md. Zakiul Alam (BMC, 2022)
Abstract Introduction Adolescence is a critical period characterized by significant physical, emotional, cognitive, and social changes, including the monthly occurrence of menstruation of adolescent girls. Despite being an inevitable natural event, most societies consider menstruation and menstrual blood as taboos and impure. Such consideration prevents many adolescent girls from proper health education and information related to menstrual health, which forces them to develop their ways of managing the event. This study attempted to explore the pattern, the urban-rural differences, and the determinants of menstrual hygiene management practices (MHMP) among adolescent girls in the Rajshahi division, Bangladesh. Methodology Using a cross-sectional study design with multistage random sampling, we collected data from 586 adolescent girls (aged 14-19 years) from the Rajshahi division of Bangladesh. The MHMP was measured using eight binary items, where the value from zero to five as 'bad,' six as 'fair,' and seven-eight as 'good' practices. Finally, we employed bivariate analysis and multinomial logistic regression analysis. Findings Only 37.7% continuously used sanitary pads. Among the cloth users, nearly three-fourths reused cloths, and about 57% used water and soap to wash them. About 49% changed menstrual absorbent, and 44% washed their genitalia three times daily. About 41% used water only to wash genitalia, and 55% buried sanitary materials under the soil. Around 36.9% of the girls practiced bad, 33.4% fair, and 29.7% good menstrual management. We found significant differences in MHMP among adolescent girls between urban and rural areas (32.3% vs. 27.7% good users, p ≤ 0.05). Multinomial logistic regression found that place of residence, age, family size, parental education, and age at first menstruation were the significant determinants of MHMP. Conclusion Although there are some cases of sanitary pad use, still menstrual hygiene management is unhealthy in most cases. The continuous supply of sanitary pads at affordable cost, change in existing social norms about menstruation, proper education, information, and services are essential for achieving health-related SDG goals in both rural and urban areas of Bangladesh.